LMPLEMENTASI SNI 7330:2009 PERPUSTAKAAN PERGURUAN TINGGI PADA UNIT PELAYANAN TEKNIS (UPT) PERPUSTAKAAN UNIVERSITAS LANCANG KUNING, PEKANBARU - Yuhelmi, Yuhelmi (Universitas Lancang Kuning, 2014)
This study aims to uncover the implementation and realization of SNI 7330: 2009 at Lancang Kuning University Library Unit(UPT) Pekanbaru, where the Lancang Kuning University Library Unit has been established in 1983. This is done to find out whether SN! 73 30:2009. Is fully implemented it this study will answer the problems that exist in the implementation activities, so as to serve the needs of visitors in the learning process (P BM) in college. In addition, this study also aims to encourage the university to pay more attention in order to achieve standardization in university learning objectives that can be a model for 9 (nine) libraries faculties in the University Lancang Kuning Pekanbaru.